2022
DOI: 10.1177/15330338221135724
|View full text |Cite
|
Sign up to set email alerts
|

Linking GOLPH3 and Extracellular Vesicles Content—a Potential New Route in Cancer Physiopathology and a Promising Therapeutic Target is in Sight?

Abstract: Golgi phosphoprotein 3 (GOLPH3), a highly conserved phosphatidylinositol 4-phosphate effector, is required for maintenance of Golgi architecture, vesicle trafficking, and Golgi glycosylation. GOLPH3 overexpression has been reported in several human solid cancers, including glioblastoma, breast cancer, colorectal cancer, nonsmall cell lung cancer, epithelial ovarian cancer, prostate cancer, gastric cancer, and hepatocellular carcinoma. Although the molecular mechanisms that link GOLPH3 to tumorigenesis require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…GOLPH3 is believed to promote cancer cell growth, inhibit cell death, and enhance migration through the regulation of signaling pathways like AKT/mTOR (Yu et al, 2020). These findings position GOLPH3 as a promising target for cancer therapy, offering novel avenues for treatment (Giansanti and Piergentili, 2022). Our study contributes to a comprehensive understanding of GOLPH3's role in colon cancer, particularly its network of effects.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…GOLPH3 is believed to promote cancer cell growth, inhibit cell death, and enhance migration through the regulation of signaling pathways like AKT/mTOR (Yu et al, 2020). These findings position GOLPH3 as a promising target for cancer therapy, offering novel avenues for treatment (Giansanti and Piergentili, 2022). Our study contributes to a comprehensive understanding of GOLPH3's role in colon cancer, particularly its network of effects.…”
Section: Discussionmentioning
confidence: 73%
“…observed that BPA exposure in mice models altered the immune microenvironment of breast cancer and promoted lung metastasis. GOLPH3, a recently discovered molecule, has emerged as a player in cancer progression (Giansanti and Piergentili, 2022). Multiple studies have reported the upregulation of GOLPH3 in various cancers, strongly associating it with tumor advancement, metastasis, and patient prognosis (Kuna and Field, 2019;Song et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations